Деякі міркування з приводу есея Алоїза Ріґля «До питання про теперішній культ пам’ятників...» - Шліпченко, С. (Студії мистецтвознавчі, 2009)
The paper explores Riegl’s concepts of intentional and un-intentional monument, idea of age value and Kunstwollen as put forward in his seminal work «The Modern Cult of Monuments: Its Character and Its Origin» (1903), its relevance for today’s scholarship. The emphasis is made on conceptual difference between monument and historical monument: while the former is regarded as a kind of quasi-universal idea related to our understanding of time and space, the latter appears as having quite distinct time (origin) and space (region) parameters, which in turn results in our approaches to conservation and renovation of historical heritage or the ways we see and support our identities in contemporary world.